Design, facile synthesis, molecular docking, DNA binding, and cytotoxic activity of polythiophene and polythiophene-titanium(IV) phosphate nanocomposite. Issue 5 (24th March 2017) - Baig, Umair; Gondal, M. A.; Alam, Md. Fazle; Alam, Mahboob; Wani, Waseem A.; Younus, Hina
ABSTRACT: The present article reports the synthesis of polythiophene-titanium(IV) phosphate nanocomposite (PTh-TiP) by a simple in situ titanium(IV) phosphate assisted chemical polymerization of thiophene. The structure and formation of polymer and its nanocomposite was confirmed by FTIR, XRD, FE-SEM, TEM, and TGA techniques. UV-Visible, fluorescence, and circular dichroism spectrophotometry as well as viscometry and DNA melting studies were used to investigate the DNA binding of PTh and PTh-TiP with calf-thymus DNA. The anticancer activities of these materials against MCF-7 and MDA-MB- 231 cancer cells indicated both PTh and PTh-TiP are moderately active, with the latter being more active than the former. GRAPHICAL ABSTRACT: